2018
DOI: 10.3389/fmicb.2018.00686
|View full text |Cite
|
Sign up to set email alerts
|

The Virome and Its Major Component, Anellovirus, a Convoluted System Molding Human Immune Defenses and Possibly Affecting the Development of Asthma and Respiratory Diseases in Childhood

Abstract: The microbiome, a thriving and complex microbial community colonizing the human body, has a broad impact on human health. Colonization is a continuous process that starts very early in life and occurs thanks to shrewd strategies microbes have evolved to tackle a convoluted array of anatomical, physiological, and functional barriers of the human body. Cumulative evidence shows that viruses are part of the microbiome. This part, called virome, has a dynamic composition that reflects what we eat, how and where we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 78 publications
1
71
0
1
Order By: Relevance
“…Another association of the virome with the immune status can be drawn through Anelloviruses, which have been linked to functional immune competence [69][70][71][72][73] . We report that Anelloviruses are a stable component of the upper airway virome, as in other systems 69,[74][75][76] 75 . Notably, we have previously demonstrated that rhinoviruses are also encoded by genomes of extremely low CpG content which can influence TLR9-dependent stimulation [78][79][80][81][82] .…”
Section: Dysbiotic Structure Of the Asthmatic Viromementioning
confidence: 62%
“…Another association of the virome with the immune status can be drawn through Anelloviruses, which have been linked to functional immune competence [69][70][71][72][73] . We report that Anelloviruses are a stable component of the upper airway virome, as in other systems 69,[74][75][76] 75 . Notably, we have previously demonstrated that rhinoviruses are also encoded by genomes of extremely low CpG content which can influence TLR9-dependent stimulation [78][79][80][81][82] .…”
Section: Dysbiotic Structure Of the Asthmatic Viromementioning
confidence: 62%
“…In previous studies, viruses from this family have been identified as the most abundant and frequent in healthy children [6,29,31,33,4145], being more abundant during the first year of life [5,29,42], after which the abundances decrease. Their presence has been associated with a reduced host immune status; a higher abundance have been reported in patient with lung transplantation [46,47], AIDs [48], pulmonary diseases [49,50], cancer [51], among others; although their role in the pathogenesis of these diseases remains unclear [52]. Our results showed that anelloviruses were significantly more abundant in the second semester of life compared with the first one (P-value 0.01, S6 Table), specially TTV like mini virus and torque teno virus species.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthy lungs of the LRT, there are six dominant bacterial phyla: Firmicutes (including genera Streptococcus and Veillonella), Bacteroides (including genus Prevotella), Proteobacteria, Fusobacteria, Acidobacteria, and Actinobacteria (including Tropheryma whipplei) (Segal et al, 2016;Dickson et al, 2015Dickson et al, , 2017. The virome of the healthy lungs contains members of the Anelloviridae family and a high frequency of various bacteriophages (Abbas et al, 2017;Willner et al, 2009;Jankauskait _ e et al, 2018), but their abundance is greater in the context of immunosuppression and/or chronic disease (Freer et al, 2018), suggesting that immunocompetence is a prerequisite to the low abundance and biodiversity of LRT virome. The lung mycobiome is composed of Eremothecium, Systenostrema, and Malassezia genera and the Davidiellaceae family (Charlson et al, 2012;van Woerden et al, 2013).…”
Section: Asthma Is Not a Single Diseasementioning
confidence: 99%
“…Although viral infections are known to be a primary cause of asthmatic exacerbations, the relationship between viruses and asthma is not completely understood, partly because of continuously evolving knowledge about the healthy virome of the respiratory tract. It has been observed that the composition and abundance of the URT and LRT virome differs among healthy subjects and asymptomatic and symptomatic patients with chronic respiratory diseases, but detailed longitudinal studies are needed for better comprehension of the causal relationships (Sundell et al, 2019;Freer et al, 2018). Complex interactions between viruses and additional environmental and intrinsic factors are probably responsible for the longer but transient presence of some viruses in the respiratory tract of asthmatic patients or the development of fully blown infections leading to severe exacerbations (Vandini et al, 2019;Sarna et al, 2018).…”
Section: Virions Readily Colonize the Lungsmentioning
confidence: 99%